1990
DOI: 10.1115/1.2927679
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Density Ratio on the Heat Transfer Coefficient From a Film-Cooled Flat Plate

Abstract: The effect of density ratio of cooling films on the heat transfer coefficient on a flat plate is investigated using a heat-mass transfer analogy. The experimental technique employed uses a swollen polymer surface and laser holographic interferometry. A density ratio of 1.0 was achieved using air as the injectant. Density ratios of 1.38 and 1.52, representative of turbine operating conditions, were obtained by using foreign gases. The coolant fluids were injected at various blowing rates through a single normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(23 citation statements)
references
References 0 publications
1
22
0
Order By: Relevance
“…A film cooling process depends on many parameters. Primary physical properties, that influence film cooling, are: a coolant-to-hot mainstream velocity ratio, blowing ratio [2], momentum ratio, pressure ratio, temperature ratio, density ratio and turbulence intensity [3][4]. Also, the geometrical characteristics have a bearing on film cooling.…”
Section: Introductionmentioning
confidence: 99%
“…A film cooling process depends on many parameters. Primary physical properties, that influence film cooling, are: a coolant-to-hot mainstream velocity ratio, blowing ratio [2], momentum ratio, pressure ratio, temperature ratio, density ratio and turbulence intensity [3][4]. Also, the geometrical characteristics have a bearing on film cooling.…”
Section: Introductionmentioning
confidence: 99%
“…One density ratio matching method used by such researchers as Sinha et al [3] involves very cold air coolant in conjunction with room temperature freestream air. Another method involves the use of a heavier foreign gas such as CO 2 for the coolant as described by Ammari et al [4]. Studies such as that by Pietrzyk et al [5] have considered density ratio effects on film cooling hydrodynamics to help determine which scaling parameters best account for density ratio differences.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous numerical studies seem to pay less attention to HTC than η presumably because (1) η is the widely-accepted parameter representing film-cooling performance and (2) the numerical prediction of η is more straightforward than those of HTC. In experimental studies, on the other hand, the details of HTC are reported frequently such as by Kumada et al (8) , Goldstein and Taylor (9) and Cho and Goldstein (10) for the region near the cooling hole and by Hay et al (11) , Ammari et al (12) , Goldstein et al (13), and Baldauf et al (14) in a region up to the far wake of the cooling hole. These previous experimental studies presented the effects of various factors such as blowing and density ratios, blowing and compound angles and spanwise pitches between holes on the HTC characteristics.…”
Section: Introductionmentioning
confidence: 99%